Analisis Resepsi Followers Akun Instagram @jurnaliskomik Terhadap Konten Berita Berbasis SARA - Dewi, Saffira Nusa; Gelgel, Ni Made Ras Amanda; Pradipta, Ade Devia; Damasemil, Calvin (E-Jurnal Medium, 2024)
One of the information on social media that is still consumed by Indonesian people is SARA. In addition to being used to share photos or videos, Instagram is also a provider of news content which does little to discuss SARA. Equipped with a comment feature, audiences can express their opinions about the information they receive. This study aims to determine the reception of followers of the Instagram account @jurnaliskomik on SARA-based news content and classify them according to the three audience positions put forward by Stuart Hall. The type of research used is qualitative research with reception analysis theory. The results of this study indicate that there is a critical attitude of the audience which can be seen from the number of comments. Related to Stuart Hall's three audience positions, the writer finds that most of the audiences who provide comments are in a Dominant Hegemonic position. This is because the average @jurnaliskomik account followers have fanaticism towards the content produced by @jurnaliskomik.